2005
DOI: 10.1128/jcm.43.5.2125-2132.2005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Macrolide-Resistant Isolates of Streptococcus pneumoniae Collected from Blood and Respiratory Specimens in Norway

Abstract: Norway has a low prevalence of antimicrobial resistance, including macrolide-resistant Streptococcus pneumoniae (MRSP). In a nationwide surveillance program, a total of 2,200 S. pneumoniae isolates were collected from blood cultures and respiratory tract specimens. Macrolide resistance was detected in 2.7%. M-type macrolide resistance was found in 60% of resistant isolates, and these were mainly mef(A)-positive, serotype-14 invasive isolates. The erm(B)-encoded macrolide-lincosamide-streptogramin B (MLS B ) ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 49 publications
0
12
0
2
Order By: Relevance
“…In fact, the increasing rates of macrolide resistance in the United States in recent years have been directly linked to the emergence of efflux-mediated resistance (8). Although once not very common, efflux-mediated macrolide resistance is not only now present at significant rates in Germany and Italy (6,16,20) but also predominates in European countries, such as Greece, Norway, and Scotland (1,15). Recent work has shown that the efflux mechanism of resistance in S. pneumoniae responsible for acquired macrolide resistance can be distinguished as either mef(E) or mef(A) (6,8,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the increasing rates of macrolide resistance in the United States in recent years have been directly linked to the emergence of efflux-mediated resistance (8). Although once not very common, efflux-mediated macrolide resistance is not only now present at significant rates in Germany and Italy (6,16,20) but also predominates in European countries, such as Greece, Norway, and Scotland (1,15). Recent work has shown that the efflux mechanism of resistance in S. pneumoniae responsible for acquired macrolide resistance can be distinguished as either mef(E) or mef(A) (6,8,25).…”
Section: Discussionmentioning
confidence: 99%
“…Since it has been reported that both mef(A) and mef(E) genes are located on different genetic elements in S. pneumoniae that may influence the dissemination of M-phenotype macrolide resistance among streptococcal and other species, it has been suggested that the two genes remain separate (11). Generally, mef(A) predominates in Europe (1,2,6,15) and mef(E) predominates in North America and Asia (5,25). However, countries such as The Netherlands and Italy have reported that as many as 30% to 40% of macrolide-resistant S. pneumoniae isolates contain mef(E) (17).…”
Section: Discussionmentioning
confidence: 99%
“…Forty-four strains (2.7%) showed reduced susceptibility to erythromycin (MIC Ն 1 mg/liter) and were further investigated. Antimicrobial susceptibility testing and determination of macrolide resistance phenotype and genotype and tetracycline resistance genotype was performed as previously described (9,16,25,32,33,37,38). Subtyping of mef was achieved by BamHI digestion of the 346-bp mef amplicon (22).…”
Section: Two Classes Of Methylase Genes Erm(b) and Erm(a) Subclassmentioning
confidence: 99%
“…The regional dissemination of the M type ST39 clone in both high-and low-consumption countries is intriguing, and the selective advantage of this clone warrants further studies. Furthermore, mef(A) was recently shown to predominate among macrolide resistant S. pneumoniae in Norway (16). The evolutionary mechanism(s) for the successful spread of this efflux mechanism between streptococci remain(s) to be elucidated.…”
Section: Erm(b) and Mef(o) Were Exclusively Associated With Tet(m) Wmentioning
confidence: 99%
“…However, resistance to erythromycin in systemic pneumococcal isolates has increased from 2.7% in 2002 to 12.4% in 2006 (33). This rapid increase in erythromycin resistance was found to be caused mainly by the spread of the England 14 -9 clone, carrying the mef(A) gene (29,44).…”
mentioning
confidence: 99%